Darwin's God evolution and the problem of evil - Hunter, Cornelius G. (Grand Rapids, MI Baker, 2001)
Includes bibliographical references and index.
Keywords: Darwin, Charles Robert, -- 1809-1882.; Evolution -- religious aspects -- Christianity